Independensi Lembaga Pemerintah dalam Penanganan Kasus Tindak Pidana Korupsi di Indonesia - Helin Kristikaningwulan; Cornellia Adinda Putri Watun; Al Makki Ahmad Hartori; Yuanda Alyansyah Putra, Y. L; Suta Ramadan (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2025)
Corruption remains a significant concern in Indonesia, exemplified by the case of former Supreme Court Judge Zarof Ricar, suspected of acting as a case broker. This case began with the arrest of three Surabaya district court judges on October 20, 2024, for allegedly accepting bribes to free Ronald Tannur. Misconceptions that winning court cases requires significant costs have created opportunities for fraud, with individuals claiming they can guarantee favorable outcomes. The Zarof Ricar case highlights the declining integrity of government institutions and the lack of synergy among law enforcement, contributing to the prevalence of corruption. This situation underscores the urgent need for comprehensive legal reform. Strengthened regulations, stricter internal supervision, and harsh penalties for corrupt practices are essential to restoring public trust in the legal system and improving institutional integrity. This study aims to provide insights by employing juridical-normative and empirical methods, utilizing literature, legal documents, observations, and interviews.